Analisis Sanitasi Lingkungan terhadap Kejadian Diare pada Balita di Kelurahan Sekar Jaya Kabupaten OKU - Siti Nurjanah; Akhmad Dwi Priyatno; Santi Rosalina (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
The morbidity and mortality rate due to diarrhea is relatively high. Several surveys in Indonesia show that diarrhea morbidity rates for all age groups are around 120-360 per 1000 population. Of the 18 Community Health Centers in OKU District, the UPTD Sekar Jaya Health Center is one of the Health Centers with the highest cases of diarrhea in toddlers. This study aims to determine the analysis of environmental sanitation on the incidence of diarrhea in toddlers. The research design used was cross sectional. The study population was all houses with toddlers who lived in Sekar Jaya Village, Working Area of the UPTD Sekar Jaya Health Center, OKU Regency, totaling 146 toddlers with a sample size of 107. The statistical tests used were chi square and logistic regression. Based on univariate analysis, the results showed that 41 respondents (38.3%) had diarrhea, there were 29 respondents (27.1%) with clean water quality who did not meet the requirements, there were 48 respondents (44.9%) with latrines that did not meet the requirements. There were 65 respondents (60.7%) did not provide trash cans and there were 41 respondents (38.3%) with the type of house floor that did not meet the requirements. The results of the bivariate analysis showed that there was a significant relationship between the quality of clean water and the incidence of diarrhea in toddlers with a p value of 0.000, there was a significant relationship between healthy latrines and the incidence of diarrhea in toddlers with a p value of 0.004, there was a significant relationship between the availability of trash cans and the incidence of diarrhea in toddlers with p value 0.002 and there is a significant relationship between the type of house floor and the incidence of diarrhea in toddlers with a p value of 0.000. The clean water quality variable is the most dominant variable affecting the incidence of diarrhea in toddlers with a p value of 0.000 and OR = 67.968.